Vision science literature of Nepal in the database “Web of Science” - Risal, S; Prasad, H N (Nepalese Journal of Ophthalmology, 2012)
Introduction: Vision Science is considered to be a quite developed discipline in Nepal, with much research currently in progress. Though the results of these endeavors are published in scientific journals, formal citation analyses have not been performed on works contributed by Nepalese vision scientists. Objective: To study Nepal’s contribution to vision science literature in the database “Web of Science”. Materials and methods: The primary data source of this paper was Web of Science, a citation database of Thomas Reuters. All bibliometric analyses were performed with the help of Web of Science analysis service. Results: In the current database of vision science literature, Nepalese authors contributed 112 publications to Web of Science, 95 of which were original articles. Pokharel GP had the highest number of citations among contributing authors of Nepal. Hennig A contributed the highest number of article as a first author. The Nepal Eye Hospital contributed the highest number of articles as an institution to the field of Vision Science. Conclusion: Currently, only two journals from Nepal including Journal of Nepal Medical Association (JAMA) are indexed in the Web of Science database (Sieving, 2012). To evaluate the total productivity of vision science literature from Nepal, total publication counts from national journals and articles indexed in other databases such as PubMed and Scopus must also be considered. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6548 Nepal J Ophthalmol 2012; 4 (2): 303-308